FIMICS: A panel of long noncoding RNAs for cardiovascular conditions. Issue 1 (January 2023) - Firat, Huseyin; Zhang, Lu; Baksi, Shounak; Leszek, Przemyslaw; Schordan, Eric; Ounzain, Samir; Kottwitz, Jan; Patriki, Dimitri; Heidecker, Bettina; Lüscher, Thomas F.; Pedrazzini, Thierry; Devaux, Yvan; et al.
Summary: Cardiovascular disorders such as heart failure are leading causes of mortality. Patient stratification via identification of novel biomarkers could improve management of cardiovascular diseases of complex etiologies. Long-noncoding RNAs (lncRNAs) are highly tissue-specific in nature and have emerged as important biomarkers in human diseases. In this study, we aimed to identify cardiac-enriched lncRNAs as potential biomarkers for cardiovascular conditions. Deep RNA sequencing and quantitative PCR identified differentially expressed lncRNAs between failing and non-failing hearts. An independent dataset was used to evaluate the enrichment of lncRNAs in normal hearts. We identified a panel of 2906 lncRNAs, named FIMICS, that were either cardiac-enriched or differentially expressed between failing and non-failing hearts. Expression of lncRNAs in blood samples differentiated patients with myocarditis and acute myocardial infarction. We hereby present the FIMICS panel, a readily available tool to provide insights into cardiovascular pathologies and which could be helpful for diagnosis, monitoring and prognosis purposes.